Peran Mediasi Ukuran Dewan dan Manajemen Modal Kerja dalam Tata Kelola Perusahaan Terhadap Kinerja Perusahaan - Alfarobi, Abdul Qodir Jailani; Diana, Nur; Afifudin, Afifudin (Universitas Islam Malang, 2024)
This research aims to analyze the mediation roles in board size and management of capital on the relationship between the corporate governance (independent commissioners and ownership structure) and company performance (ROA and ROE) at manufacturing companies in the consumer goods industry sectors that are listed in Indonesia stock exchange in the period of 2020-2023. Research using a quantitative approach with Partial Least Square (PLS) analysis techniques. The research sample totaled 180 data from 45 companies selected using purposive sampling method. These results shows that an independent commissioner and ownership structure has a positive and significant effect on both ROA and ROE. Working capital management is proven to positively and significantly mediate the relation between the independent commissioner and ownership structure with ROA and ROE. However, board size is not shown to mediate the relationship between independent commissioners and ownership structure with ROA and ROE. This study provides empirical evidence of the important role of working capital management in strengthening the influence of corporate governance on financial performance.Keywords: Corporate governance, firm performance, board size, working capital management